Trajectoire d’insertion socioprofessionnelle de femmes sous l’angle des variables personnelles et sociales - LeBreton, Diane (Canadian Journal of Counselling and Psychotherapy, 2009)
This article explores women’s career paths by looking at the influences affecting their social and professional integration. Information from 27 participants was collected using a psychosocial approach. This study reveals nine closely related variables that affect the participants’ process: sexual and professional stereotypes, discrimination, number of roles, structural elements of the labour market, linguistic characteristics, identity formation, elements related to the self, education, and socialization.